Observational evidence of enhanced middle/upper tropospheric ozone via convective processes over the equatorial tropical Atlantic during the summer of 2006 - Gregory S. Jenkins; Moctar Camara; Seydi A. Ndiaye (Geophysical Research Letters)
Biomass burning in Central Africa or lightning in West Africa may serve as mechanisms to enhance tropospheric ozone (O3) during Northern Hemisphere summer (JJA) in Equatorial latitudes. During the summer of 2006, ozonesondes launched from the Ronald H. Brown research cruise in equatorial latitudes (5°N–5°S) along 23°W showed elevated concentrations of O3 in the middle and upper troposphere. The total column ozone (TCO) increased by a factor of 1.2 between Legs 1 (June 11–15) and Legs 2 (June 26–29) from 36.5 to 43.5 DU. Nearly 80% of the TCO ozone was found above 700 hPa and only 10% of the TCO was found between the surface and 850 hPa. Consequently this implies that two mechanisms are responsible for elevated O3: (1) lightning associated with organized convective systems in West Africa which produced O3 via NOX, (2) a northward transport of biomass burning constituents from central Africa over land into regions of deep convection followed by the vertical transport of O3 and O3 precursors to the middle/upper troposphere. While O3 and O3 precursors are transported directly from Central Africa to the tropical Eastern Atlantic near the surface, the stability of the atmosphere inhibits vertical transport to the free troposphere.